2019
DOI: 10.4103/jlp.jlp_76_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of prognostic utility of Ki-67, P53, and O-6-methylguanine-DNA methyltransferase expression in pituitary tumors

Abstract: BACKGROUND OR CONTEXT: Pituitary adenoma (PA) is the most common pathology of the pituitary gland. Pituitary tumors were historically considered benign, however, from recent advances in pathological and molecular analyses, numerous prognostic markers have been identified, allowing a better characterization of tumor behavior and prediction of response to treatment and recurrences. AIMS AND OBJECTIVES: Evaluation of the epidemiological occurrence of pituitary tumors in our center and prediction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…However, another study (50) reported an inverse relationship between the Ki-67 index and Knosp grade for functional PA and nonfunctional PA (R= -0.59, p < 0.001 in functional PA and R = 0.367, p < 0.01 in nonfunctional PA). Das et al found no significant correlation between Knosp grade and Ki-67 index (5). In the current research, PAs with the Knosp grades 0-2 and grades 3-4 were classified into noninvasive and invasive classes.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, another study (50) reported an inverse relationship between the Ki-67 index and Knosp grade for functional PA and nonfunctional PA (R= -0.59, p < 0.001 in functional PA and R = 0.367, p < 0.01 in nonfunctional PA). Das et al found no significant correlation between Knosp grade and Ki-67 index (5). In the current research, PAs with the Knosp grades 0-2 and grades 3-4 were classified into noninvasive and invasive classes.…”
Section: Discussionmentioning
confidence: 57%
“…PA is the most common tumor in the sellar region (1), and high Ki-67 suggests invasive growth and worse prognosis for patients with PAs (2,5). Preoperative prediction of Ki-67 could further assist neurosurgeons to develop better, more individualized treatment strategies for patients with PAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, although the PAs were benign, some neoplasms still demonstrated invasive or aggressive growth, and tumor recurrence was observed during the postoperative follow up [ 11 ]. The Ki-67 index is considered a biomarker of aggressive tumor behavior, which is related to the invasiveness, aggressiveness, and recurrence of PAs [ 12 ]. Series studies have shown that a higher Ki-67 index is associated with a higher cell proliferation rate and more aggressive behavior in PAs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tendency to relapse has been related to many factors, including different histotypes, tumor remnants, or the extent of invasion into adjacent anatomical structures (6). Previous research has demonstrated that many clinicopathological prognostic tools have potential to predict the recurrence of PMA, consisting of IHC characteristics, invasion of tumors, genetic expression, and markers of proliferation (7)(8)(9)(10)(11). However, very few attempts have been made to integrate these risk factors with a machinelearning approach.…”
Section: Introductionmentioning
confidence: 99%